Outcome of arthroscopic vs mini open subacromial decompression in treating shoulder impingement syndrome - Nik Abdul Adel, Nik Alyani; Siron @ Baharom, Khairul Nizam; Mat Lani, Muhammad Taufik (2018)
Introduction:Shoulder impingement syndrome is a common diagnosis leading to shoulder disabilities.Subacromial decompression surgery either arthroscopic or mini open is indicated in patients who failed conservative therapy.Arthroscopic surgery is introduced to reduce soft tissue dissection hence less soft tissue damage and fasten rehabilitation.This study is conducted to compare the outcomes of mini open and arthroscopic surgery.Materials and method:A cross sectional study was conducted in patients who was diagnosed with shoulder impingement syndrome with or without rotator cuff tear who had underwent subacromial decompression surgery, with mini open or arthroscopic surgery in Hospital Tengku Ampuan Afzan, Kuantan.Functional outcome is assessed using American Shoulder and Elbow Surgeon (ASES) score and Constant score.Results:6 patients were recruited in mini open group while 11 in arthroscopic group.Of this, all were female in mini open group, aged 56.7±7.9 while 7 female and 4 male in arthroscopic group aged 55.09 ± 9.35(p-value 0.7325).They were evaluated at 3 to 5 years after surgery in mini open while at 6 months in arthroscopic group.There was no significant different of ASES score in mini open group(89.8±11.7) and arthroscopic group(89.809±17.9), with p-value of 0.998. Constant score in mini open is 18.67±7.61 while in arthroscopic is 16.18±15.03; and there is no significant different in this two groups(p-value 0.712).3 patients each has good and fair outcome in mini open, while 6 patients has excellent, 2 each has good and  fair; and 1 has poor outcome in arthroscopic.Conclusion:There were no significant differences in functional outcome in between mini open or arthroscopic subacromial decompression surgery.